STRATEGI MENINGKATKAN MINAT BELAJAR AL-QUR'AN PADA ANAK DENGAN METODE QUR'ANI SIDOGIRI DI MADRASAH DARUS SALAM DRINGU PROBOLINGGO - mukarromah, Lu'luil Mukarromah; Nakib, M. Nakib Hasyim; Hasbullah, M. Hasbullah Marzuki; Eka, Eka Sri Wahyuni; Prasetiya, Benny (DEVELOPMENT: Journal of Community Engagement, 2024)
This research explores the interest of the younger generation in learning the Quran, with a focus on the Sidogiri Qur'anic Method (MQS) at Madrasah Darus Salam Dringu Probolinggo. The background highlights the uniqueness of the Quran and the shift in students' activities in reading it. The aim of this research is to describe how Quranic learning in the madrasah is planned using MQS, with the hope of enhancing students' interest in learning. Through survey methods, questionnaires, and the participation of MQS teaching staff, this research is expected to provide a positive contribution. The steps involve initial surveys, contacting the foundation's head, scheduling, and interaction with teaching staff. The results show an improvement in children's understanding of the Quran, while MQS focuses on technical learning and the formation of Islamic character. The conclusion affirms MQS as a comprehensive effort to shape individuals with strong religious knowledge and Islamic character. Recommendations include recognition, teacher empowerment, and more efficient scheduling for the sustainability of the research. Keywords: Strategy; Quran; Sidogiri Qur'anic Method